Aneurisma trombosado de arteria comunicante anterior asociado a síntomas visuales - Preciado Mesa, Esteban; Ayala Villegas, Ana Cristina; Moreno Duque , Oscar Eduardo; Llano Naranjo , Yuliana; Londoño Ocampo, Francisco Javier (Revista Argentina de Neurocirugía, 2021)
ABSTRACT Introduction: Aneurysms of the anterior communicating artery (AComA) frequently present as a cause of spontaneous subarachnoid hemorrhage (HSAE), in rare cases they are associated with visual symptoms due to mechanical compression or rupture and their surgical treatment often represents a challenge. Case report: The clinical case of an adult patient with a visual acuity decrease by the right eye of temporal predominance and findings in cerebral MRI and angiography compatible with a large AcomA aneurysm associated with partial thrombosis are presented; clipping and thrombectomy of the aneurysm is performed, in the control panangiography a complete clipping of the lesion is evident. Discussion: The visual deficit in an intracranial aneurysm can be associated with multiple mechanisms, among them the rupture of the aneurysm towards the optic nerve with the subsequent formation of a hematoma, adhesions and fibrosis, or more rarely by mechanical compression of an unrupted giant aneurysm. Surgical management often involves complex microsurgical techniques to try to resolve the mass effect and exclude the aneurysm, in this case it is possible to resolve the mass effect and completely exclude the aneurysm with improvement of the visual symptoms in the patient. Conclusion: Aneurysms of the anterior communicating artery (AcomA) in rare cases can be associated with visual symptoms such as decreased visual acuity, and microsurgical techniques offer an effective method to alleviate the mass effect and improve visual symptoms.